Managing participation and turn-taking in children’s digital activities: Touch in blocking a peer’s hand - Jakonen, Teppo; Niemi, Kreeta (Social Interaction. Video-Based Studies of Human Sociality, 2020)
This article investigates touch in the social organization of digital classroom activities as small groups of primary school pupils animate a story by using a shared iPad. Such a socio-material setting foregrounds haptic resources for action and requires coordination of hand movements on and around the screen. The groups in our data treat the animation as a product that takes its shape through the individual members operating the device one at a time. Our analysis focuses on how the haptic practice of blocking a peer’s hand is deployed to manage competition for a turn at using the tablet and to resolve the problem of its simultaneous manual operation by two or more participants. The blocks we describe are non-intensive human-to-human touches with varying duration whereby one participant prevents another from accessing the screen by sweeping the latter’s hand aside or grabbing and holding it. We show through a multimodal analysis how blocks accomplish the social action of claiming a turn for the blocker by investigating how they emerge sequentially, how participants operating the tablet anticipate peer interruption with ready-to-block hand movements, and how blocks are complied with or resisted. In our conclusion, we consider to what extent the young children in our data treat blocks as morally problematic and socially controlling actions, and how digital technologies shape educational practices.